PENGARUH PENERAPAN METODE PENEMUAN (DISCOVERY) TERHADAP HASIL BELAJAR MATEMATIKA KELAS VIII SMP TRI SUKSES NATAR - Nurdin, Ahmat (Epsilon: Jurnal Pendidikan Matematika, 2020)
This study aims to analyze the effect of applying the discovery method to the mathematics learning outcomes of Grade VIII students of SMP Tri Sukses Natar even semester of the 2018/2019 academic year. The method used in this research is the experimental method. The independent variable in this study is the discovery method and the dependent variable in this study is the mathematics learning outcomes. This research was conducted in eight meetings in the even semester of the 2018/2019 academic year. All students of class VIII of SMP Tri Sukses Natar totaling 102 students became the population in this study. The sampling technique used in this study is cluster random sampling technique. The sample used in this study is class VIII A as an experimental class and class VIII B as a control class. The discovery method is applied in the learning process of the experimental class, whereas conventional learning is applied in the control class. Data collection in this study used a test technique. The instrument used in the form of essay questions consisted of ten items that had to be done by students at the end of the learning process. Based on the results of calculations and discussions, it can be concluded that there is an influence on the application of the discovery method to the mathematics learning outcomes of VIII grade students of SMP Tri Sukses Natar even semester of the 2018/2019 academic year.